8 - Existe-t-il un effet genre dans les performances académiques des étudiants dans les facultés des sciences économiques et de gestion au Cameroun ? Cas de la FSEG de l’université de Yaoundé II - Atala, Étienne (Journal of Higher Education in Africa, 2022)
The objective of this research is to determine whether there is a gender effect in the performance of students in the Faculty of Economics and Management of the University of Yaounde 2. Student performance is studied from two perspectives: selectivity and exam success. We used a flow analysis and a sequential multinomial model to study this performance. Using the 2015-2016 student cohort of 2,488 individuals, the results show that the performance gap in this faculty is gendered in favour of girls. The latter have a lower selectivity rate than men; moreover, their chances of success are higher than those of men at all levels of study.